The electrophysical and optical properties of gadolinium monoantimonide thin films - Jabua, Z.; Kupreishvili, I.; Gigineishvili, A.; Iluridze, G.; Minashvili, T. (Физическая инженерия поверхности, 2012)
Within a wide temperature interval 90 – 700 K the main the dependence of electro-physical parameters of GdSb films (specific resistance, Hall constant and thermo-electromotive force) on temperature have been measured. It has been shown that the films are semimetals. The reflection and adsorption spectra of prepared films have been studied for the first time within the intervals of 0.05 – 5.5 eV. On the basis of received data the diagram of the dependence of penetration real part and loss functions on the photon energy have been plotted. It has been shown that the spectra of optical parameters have quite a complex nature.